Clinical efficacy and safety outcomes of bempedoic acid for LDL-C lowering therapy in patients at high cardiovascular risk: a systematic review and meta-analysis. Issue 2 (24th February 2022) - Lin, Yingfeng; Parco, Claudio; Karathanos, Athanasios; Krieger, Torben; Schulze, Volker; Chernyak, Nadja; Icks, Andrea; Kelm, Malte; Brockmeyer, Maximilian; Wolff, Georg
Abstract : Objectives: Bempedoic acid (BA) is a novel oral low-density lipoprotein cholesterol lowering drug. This systematic review and meta-analysis aims to assess efficacy and safety for clinical outcomes in high cardiovascular (CV) risk patients. Data sources: MEDLINE, Cochrane Central Register of Controlled Trials, Google Scholar, Embase, ClinicalTrials.gov, Clinical Trial Results and the American College of Cardiology web site were searched. Study selection: Randomised controlled trials (RCTs) of BA versus placebo in high CV risk patients reporting clinical outcomes were included. Main outcomes and measures: Primary efficacy outcomes were major adverse cardiovascular events (MACE), all-cause mortality, CV mortality and non-fatal myocardial infarction (MI). Safety outcomes included new onset or worsening of diabetes mellitus (DM), muscular disorders, gout and worsening of renal function. Results: Six RCTs with a total of 3956 patients and follow-ups of four to 52 weeks were identified. Heterogeneity mainly derived from differing follow-up duration and baseline CV risk. No difference in MACE (OR 0.84; 95% CI 0.61 to 1.15), all-cause mortality (OR 2.37; CI 0.80 to 6.99) and CV mortality (OR 1.66; CI 0.45 to 6.04) for BA versus placebo was observed. BA showed beneficial trends for non-fatal MI (OR 0.57; CI 0.32 to 1.00) and was associated with a lower risk of new-onset or worsening of DM (OR 0.68; CI 0.49 to 0.94), but higher risk of gout (OR 3.29; CI 1.28 to 8.46) and a trend for muscular disorders (OR 2.60; CI 1.15 to 5.91) and worsening of renal function (OR 4.24; CI 0.98 to 18.39). Conclusion: BA in high CV risk patients showed no significant effects on major CV outcomes in short-term follow-up. Unfavourable effects on muscular disorders, renal function and gout sound a note of caution. Hence, further studies with longer term follow-up in carefully selected populations are needed to clarify the risk/benefit ratio of this novel therapy.